(3deM GdSMQ ef QhM GdTYQh QhM GdSMQs - (3CHhYKeGf SYO Hf CMeO Hf EHQGgje Hf djhf GdJLjHj GdCfOdSjs; (3GHf GdLdGHj , eMeO Hf CMeO Hf eMeO GdLdGH GdagQj, CHh YHO Gddg,J (B664 (3g` s
(3ChdgG (B:s
(3hHYO, aEf GdCOH ef CXQa eG JRjf Hg Chdh GdMSH s
(3BNQgG (B:s
(3hPdc HeOjfI GdeQjI MQSgG Gddg JYGdi aj ChGNQ QLH GdaQO ef YGe JSYI hKdGKjf hSHY eFI s
(3fSNI KGdKIs
(3JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa jSjQ aj HYV GdCdaGXs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B169 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdCOHs